Alterações morfofuncionais em ratos suplementados com óleo de farelo de arroz e submetidos a treinamento físico - Mori, Maria Letícia Giublin Teixeira Sanches (2011)
The use and ergogenic resource options in the market to increase performance in sports athletes have been growing high-intensity, parallel or not the scientific evidence. Among these options, is expanding the use rice brain oil (RBO), rich in gamma-oryzanol (Juliano et al., 2005). Studies on rice brain oil under conditions of exercise are scarce, and interval training, rare. Thus, this work aims to contribuite to an understanding of the effects of supplementation of rice bran oil on body composition and metabolism of fats. The aim of this study is to analize the morphophysiological changes in rats supplemented with rice bran oil rich in gammaoryzanol and subject to physical training on a treadmill intervals and specific objectives are to evaluate the influence of supplementation of rice bran oil in different concentration in the evolution of body weight and adiposity of sedentary and trained rats, to characterize the lipid profile through plasma levels of total cholesterol, cholesterol fractions (HDL and LDL) and triglycerides in the different experimental groups to quantify the glucose content current and muscle glycogen as biomarkers of carbohydrate, check testosterone levels resulting from the RBO supplementation and physical training, to analyze changes in muscle fiber by typing muscle and cellular areas. We used 24 male Wistar rats, 60 days, divided into six groups, SC, SG3, SG6, TC, TG3 and TG6. The interval exercise training was realized for 6 weeks. The control groups received corn oil and supplemented groups received rice bran through gavage after exercise. The results were significant reduction in final body weight in all groups, only the fatty pads in visceral fat showed significant difference, but not in all groups. In peripheral fat no significant difference was observed. There was a reduction of CT for animals TG3, LDL decreased in all groups and CT/HDL did not differ between groups, triglyceride levels were significantly lower for G3, and muscle glycogen levels had increased, and testosterone levels did not differ. In the muscle fibers, as the frequency of fibers the result found was reduce in the oxidative fibers in groups T and in glycolytic fibers SG3 had increased, and the sum total of the fibers were siginificant increases in G3. In the area of muscle fibers, type I showed no increase, in IIa only the groups SG6 and IIb all groups showed an increase, but the TC got a 53% increase. Concludes that exercise realized by treadmill and supplementation of rice bran oil rich in gamma-oryzanol (RBO) induced morphometric changes in adipose tissue and muscle. In general, the association between interval training and supplementation with RBO indicate a positive ergogenic response, but further studies are needed to expand research molecular.